Mucormycosis or black fungus: An emerging threat in COVID-19 - Bhadra, Abhishek; Ahmed, Md Sharfuddin; Rahman, Mohammed Atiqur; Islam, Samprity (Bangabandhu Sheikh Mujib Medical University Journal, 2021)
Abstract not available BSMMU J 2021; 14 (COVID -19 Supplement): 51-56